Bangladesh : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Requests for Waiver of Performance Criteria, Activation of the Trade Integration Mechanism (TIM), and Augmentation of the Access Under the PRGF Arrangement in Accordance with the TIM. (IMF Staff Country Reports; Country Report, 2004)
This paper discusses Bangladesh's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Requests for Waiver of Performance Criteria. Bangladesh's macroeconomic policies have been prudent. December 2003 quantitative targets and March 2004 performance criteria were met. Progress on structural reforms has been mixed owing to delays in implementation, with slippages in meeting most of the structural performance criteria and benchmarks. However, remedial actions have been taken, with respect to both tax administration and the process of strengthening bank management and adopting bank-by-bank resolution strategies.